Revision of Macrima Baly, 1878 (Coleoptera: Chrysomelidae: Galerucinae) - Chuan Feng; Xingke Yang; Jan Bezděk; Siqin Ge (Insects)
This study presents a taxonomic revision of the genus Macrima Baly, 1878 to advance the understanding of suprageneric, non-monophyletic “Monoleptites”. Through comprehensive morphological examinations of all type specimens, including detailed analyses of male and female genitalia and the structure of the cavitous anterior part of the head, we propose M. roseofulva Medvedev, 2011 and M. ferrugina Jiang, 1990 as new synonyms of M. aurantiaca (Laboissière, 1936), M. bifida Yang, 1992 a new synonym of M. cornuta (Laboissière, 1936), and M. yunnanensis (Laboissière, 1936) as a new synonym of M. pallida (Laboissière, 1936). In addition, M. costatipennis Jacoby, 1896 is transferred to Hoplosaenidea Laboissière, 1933 (comb. nov.). Color photos of habitus, body details, and genitalia are presented for all species.